Synthesis, Antibacterial and Antifungal Activities of 2,4-Dimethyl-3,5-diarylimino-1,2,4-thiadiazolidines and related Benzothiazolylguanidines - Pandeya S.N.; Naik P.R. (My University, 2025)
[No abstract available]